Fatal cerebral hemorrhage in a patient with thrombotic thrombocytopenic purpura with a normal platelet count during treatment with caplacizumab. (3rd April 2022) - Ditzel, Kim; Mons, Dirk Jan; Fijnheer, Rob
Abstract: Acquired thrombotic thrombocytopenic purpura (aTTP) is a thrombotic microangiopathy with a severe mortality and morbidity. Caplacizumab has recently been approved in the Netherlands as a new therapeutic option in patients with life-threatening organ failure due to aTTP. We describe the case of a 50 year old patient with aTTP who was referred to our hospital for treatment with caplacizumab. After undergoing treatment with plasmapheresis, prednisolone, rituximab and caplacizumab, her platelet count recovered and she was ready to be discharged. Unfortunately, before discharge she developed a fatal intra-cerebral hemorrhage. Fatal hemorrhage as an adverse event of caplacizumab has not been described before. Up to now there is no evidence-based treatment for caplacizumab induced heavy bleeding.